2016
DOI: 10.3390/f8010003
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Variation and Introgression of a CONSTANS-Like Gene in North American Red Oaks

Abstract: Oaks provide a model system to study maintenance of species identity by divergent selection since they maintain morphological differences and ecological adaptations despite interspecific hybridization. The genome of closely related interfertile oak species was shown to be largely homogeneous, with a few genomic areas exhibiting high interspecific differentiation possibly as result of strong divergent selection. Previously, a genic microsatellite was identified as under strong divergent selection, being nearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 40 publications
(97 reference statements)
2
33
0
Order By: Relevance
“…Characterization of the outlier locus COL in neighboring (parapatric) populations of Q. rubra and Q. ellipsoidalis from three regions (Lind‐Riehl et al, 2014; Lind‐Riehl and Gailing, 2017) showed signatures of asymmetric introgression of outlier alleles; introgression of allele 141 ( Q. rubra allele) into Q. ellipsoidalis was consistently higher than introgression of allele 138 into Q. rubra (Lind‐Riehl and Gailing, 2017). In the only sympatric population of Q. rubra , Q. ellipsoidalis , and Q. velutina , an opposite pattern was observed, introgression of allele 138 into Q. rubra was higher than introgression of allele 141 into Q. ellipsoidalis .…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…Characterization of the outlier locus COL in neighboring (parapatric) populations of Q. rubra and Q. ellipsoidalis from three regions (Lind‐Riehl et al, 2014; Lind‐Riehl and Gailing, 2017) showed signatures of asymmetric introgression of outlier alleles; introgression of allele 141 ( Q. rubra allele) into Q. ellipsoidalis was consistently higher than introgression of allele 138 into Q. rubra (Lind‐Riehl and Gailing, 2017). In the only sympatric population of Q. rubra , Q. ellipsoidalis , and Q. velutina , an opposite pattern was observed, introgression of allele 138 into Q. rubra was higher than introgression of allele 141 into Q. ellipsoidalis .…”
mentioning
confidence: 98%
“…Despite recurrent and symmetric interspecific gene flow in contact zones between both species (Lind and Gailing, 2013; Owusu et al, 2015; Lind‐Riehl and Gailing, 2017), they remain morphologically and ecologically distinct, and hybrids and introgressive forms in adult trees are relatively rare in neighboring (parapatric) populations (Lind and Gailing, 2013; Collins et al, 2015). For example, genetic assignment analyses in populations of Q. rubra and Q. ellipsoidalis in the northern range of both species, where they co‐occur as the only interfertile oak species, revealed no F 1 hybrids, 6.5% introgressive forms with Q. ellipsoidalis in Q. rubra populations, and 9.0% introgressive forms with Q. rubra in Q. ellipsoidalis populations (Lind‐Riehl and Gailing, 2017). Interspecific gene flow was also reflected in low interspecific genetic differentiation at most nuclear and genic microsatellites and sharing of regional chloroplast haplotypes between species in sympatric and parapatric populations (Lind and Gailing, 2013; Zhang et al, 2015).…”
mentioning
confidence: 99%
See 3 more Smart Citations